2014
DOI: 10.1186/1477-7819-12-259
|View full text |Cite
|
Sign up to set email alerts
|

Combined submandibular gland flap and sternocleidomastoid musculocutaneous flap for postoperative reconstruction in older aged patients with oral cavity and oropharyngeal cancers

Abstract: BackgroundThe growth of aging populations in an increasing number of countries has led to a concomitant increase in the incidence of chronic diseases. Accordingly, the proportion of older aged patients with oral cavity and oropharyngeal cancers and comorbidities has also increased. Thus, improvements must be made in the tolerance and safety of surgical procedures for these patients with complex medical conditions. In this study, we investigated combined submandibular gland flap and sternocleidomastoid musculoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The surgical method used was the same as described in formal literature. [9] 2.2.2.4. Postoperative observational indicators.…”
Section: Ethics Statementmentioning
confidence: 99%
“…The surgical method used was the same as described in formal literature. [9] 2.2.2.4. Postoperative observational indicators.…”
Section: Ethics Statementmentioning
confidence: 99%
“…Yang et al [ 9 ] used the submandibular gland flap successfully for the reconstruction of the defects in the infratemporal region after tumor resection. In addition, Zhang et al reported the usage of submandibular gland flap for the reconstruction of oral cavity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have described tissue defect reconstruction after the excision of head and neck tumors using a sternocleidomastoid muscle or myocutaneous flap as a nerve bed [1][2][3]. An advantage of this method is that it provides additional blood flow for the transplanted nerve.…”
Section: Introductionmentioning
confidence: 99%